METHOD FOR CONSTRUCTING THE TASKS OF EVALUATING THE LEARNING OUTCOMES OF TECHNICAL COLLEGE STUDENTS - Luzan , Petro; Mosya , Irina; Pashchenko , Tetiana; Yarosh , Lyubov (Professional Pedagogics, 2021)
Relevance is determined by reforming the content, methods, forms, technologies of engineering education, which is based on the competence approach and necessitates such diagnostic techniques that would effectively manage personality-oriented pedagogical interaction, objectively and reliably assess the level of mastery of components of educational and professional programs by future mechanics, technicians, technologists. Objective: to develop a methodology for designing and assessing the complexity of individual learning tasks as a step-by-step procedure based on the analysis of the conditions of the proposed educational action and indicators of the novelty of its implementation by a student of technical college. The research methodology is based on the unity of activity, system, personality-oriented and technological approaches, which has allowed to develop a student-centered, algorithmic (focused on the structure of educational activities) method of constructing individual tasks for assessing educational achievements of technical college students. Results: (on the basis of the theory of gradual formation of mental actions), indicators of the description of educational actions in sequence of their formation are allocated (the form of representation of the contents of an approximate basis of action to the performer – the presence of the operation of the transformation of the object in the approximate basis – the form of representation of the object of action – the form of transformation of the object of action – the degree of novelty of the action performed for the student); examples of constructing a system of individual learning tasks of students are given. Conclusions: the need to formalize the procedure for assessing the complexity of individual learning tasks of students by using indicators of the approximate basis of action, executive part and novelty of action for their differentiation from the simplest to complex, highly intelligent.